Plasma corin levels provide minimal prognostic utility in left atrial reverse remodeling after catheter ablation of atrial fibrillation: an observational study - Wang, Qianqian; Li, Yang; Yuan, Xiaoyang; Gong, Yue; Song, Keyi; Li, Chunkai; Liu, Jinqiu; Zhao, Yichang; Chen, Feifei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to assess the impact of plasma corin levels on left atrial reverse remodeling (LARR) in patients with atrial fibrillation (AF) after catheter ablation (CA).MethodsThis prospective, single-center, observational study included 335 patients undergoing first CA of AF. All patients underwent at least two echocardiographic examinations at intervals of ≥3 months. Corin was measured before and 1 day after CA. LARR was defined as a reduction of ≥20% in left atrial volume index.ResultsAfter a median of 29.53 months of follow-up, 94 patients exhibited LARR. The plasma corin concentrations drawn pre- and post-procedure in the LARR group were 442.85 [241.25, 631.68] and 516.83 [362.4,697.84] pg/mL, and those were significantly higher than those in the non-LARR group (393.82 [207.09, 558.11] and 473.77 [320.88, 665.75] pg/mL; P = 0.036 and P = 0.047). The Kaplan–Meier survival curve showed high baseline corin concentrations which indicated a higher rate of LARR than low corin concentrations (P = 0.014). The Cox regression found plasma corin levels before or after the procedure were not associated with LARR in AF patients after CA, with or without adjusting for confounding factors. Absence of hypertension (P = 0.001, OR = 0.33) and diabetes mellitus (P = 0.007, OR = 0.269) was associated with a greater likelihood of LARR in AF patients after CA.ConclusionsAlthough plasma corin concentrations were increased in the LARR group, it provided minimal prognostic utility in LARR after CA of AF.